1988
DOI: 10.1055/s-2007-1018145
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Early Esophageal Squamous Carcinoma and Early Adenocarcinoma of the Gastric Cardia in the People's Republic of China

Abstract: Ninety cases of early esophageal squamous carcinoma (EESC) and 27 patients with early adenocarcinoma of the gastric cardia (EAGC), who for various reasons refused surgical treatment, radiotherapy or chemotherapy, were followed up endoscopically and roentgenologically for 19 to 78 months. Of the 90 cases with EESC, 52 (58%) were still found to have superficial mucosal lesions, 8 cases progressed to an advanced stage, 27 died of cancer with an average survival time of 53.2 months, and 3 died of other non-maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…For lead time bias, we adjusted for the sojourn time, previously estimated to be approximately 3 years,12 13 and found a persisting significant effect when surveillance is compared with diagnostic endoscopy. We also hypothesised, and our analytic technique has demonstrated, that any improvement in survival would be mediated by detection of early-stage tumour and subsequent application of curative therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For lead time bias, we adjusted for the sojourn time, previously estimated to be approximately 3 years,12 13 and found a persisting significant effect when surveillance is compared with diagnostic endoscopy. We also hypothesised, and our analytic technique has demonstrated, that any improvement in survival would be mediated by detection of early-stage tumour and subsequent application of curative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sojourn time is the time for an undetected cancer to become detected; and estimated in previous studies of oesophageal cancer to be approximately 3 years 12 13. We assumed an exponential distribution of the sojourn time 14.…”
Section: Methodsmentioning
confidence: 99%
“…2, 4, 5 However, several large recently published population-based studies suggest that the progression rate is actually much lower (~0.18%). 68 The length of follow up in both designs is regularly between five to seven years.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that patients who are not candidates for surgery and in whom the clinical diagnosis of early cancer is likely may be adequately treated with endoscopic laser therapy as a sole procedure [14,15] or within a multimodality ap proach [16][17][18], The rationale for treating elderly, poorrisk patients with early esophageal cancer by means of laser therapy is supported by the observation that a period of 4-5 years is likely for an untreated carcinoma in situ to progress to advanced cancer [ 19], Furthermore, according to Miao et al [20], out of 23 patients with an untreated early cancer of the esophagus, 1 1 progressed to advanced cancer after a mean interval of 55 months, and 12 remained in the early stage for a mean period of 74 months. We have treated 10 patients with a clinical diag nosis of early esophageal cancer with PDT or YAG-laser therapy during the last 3 years of the study, and until now no patients died with neoplastic recurrence.…”
Section: Discussionmentioning
confidence: 99%